2009
DOI: 10.1016/j.iccn.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying tactile touch and gaining hope when being cared for in intensive care—A phenomenological hermeneutical study

Abstract: Summary Touch has been a part of the healing process in many civilisations and cultures throughout the centuries. Nurses frequently use touch to provide comfort and reach their patients. The aim of this study was to illuminate the meaning of receiving tactile touch when being cared for in an intensive care unit. Tactile touch is a complementary method including the use of effleurage, which means soft stroking movements along the body. The context used to illuminate the meaning of receiving tactile touch was tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…In terms of evidence for the proposed underlying mechanisms, qualitative findings by Henricson Segesten Berglund and Määttä () that sedated patients wished to be more alert to more fully enjoy the pleasure of touch supported our proposition that sedation inhibits reward processing. Further, Henricson et al reported that the participants’ awareness of missing out on a more pleasurable experience led to feelings of sadness.…”
Section: Resultsmentioning
confidence: 57%
See 4 more Smart Citations
“…In terms of evidence for the proposed underlying mechanisms, qualitative findings by Henricson Segesten Berglund and Määttä () that sedated patients wished to be more alert to more fully enjoy the pleasure of touch supported our proposition that sedation inhibits reward processing. Further, Henricson et al reported that the participants’ awareness of missing out on a more pleasurable experience led to feelings of sadness.…”
Section: Resultsmentioning
confidence: 57%
“…Further, Henricson et al reported that the participants’ awareness of missing out on a more pleasurable experience led to feelings of sadness. For example, one man recounted sadly:
“[…] it is a pity that I was not more alert during the touch […] it should have been a really good experience […] you experience pleasurable things the same time as you are sleepy…” (Henricson et al , p. 328)
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations